Bridging strategies and cardiac replacement outcomes in patients with acute decompensated heart failure‐related cardiogenic shock. (19th January 2023) - Varshney, Anubodh S.; Berg, David D.; Zhou, Guohai; Sinnenberg, Lauren; Hirji, Sameer; DeFilippis, Ersilia M.; Mallidi, Hari R.; Morrow, David A.; Rinewalt, Daniel; Givertz, Michael M.
Abstract: Aims: To describe outcomes associated with bridging strategies in patients with acute decompensated heart failure‐related cardiogenic shock (ADHF‐CS) bridged to durable left ventricular assist device (LVAD) or heart transplantation (HTx). Methods and results: Durable LVAD or HTx recipients from 2014 to 2019 with pre‐operative ADHF‐CS were identified in the Society of Thoracic Surgeons Adult Cardiac Surgery Database and stratified by bridging strategy. The primary outcome was operative or 30‐day post‐operative mortality. Secondary outcomes included post‐operative major bleeding. Exploratory comparisons between bridging strategies and outcomes were performed using overlap weighting with and without covariate adjustment. Among 9783 patients with pre‐operative CS, 8777 (89.7%) had ADHF‐CS. Medical therapy ( n  = 5013) was the most common bridging strategy, followed by intra‐aortic balloon pump (IABP; n  = 2816), catheter‐based temporary mechanical circulatory support (TMCS; n  = 417), and veno‐arterial extracorporeal membrane oxygenation (VA‐ECMO; n  = 465). Mortality was highest in patients bridged with VA‐ECMO (22%), followed by catheter‐based TMCS (10%), IABP (9%), and medical therapy (7%). Adverse post‐operative outcomes were more frequent in LVAD recipients compared with HTx recipients. Conclusion: Among patients with ADHF‐CS bridged to HTx or durable LVAD, the highest rates of death and adverse events during index hospitalization were observed in those bridged with VA‐ECMO, followed by catheter‐based TMCS, IABP, and medical therapy. Patients who received durable LVAD had higher rates of post‐operative complications compared with HTx recipients. Prospective trials are needed to define optimal bridging strategies in patients with ADHF‐CS. Abstract : In patients with acute decompensated heart failure‐related cardiogenic shock (ADHF‐CS) bridged to cardiac replacement, the need for more advanced forms of temporary mechanical circulatory support (TMCS) is associated with a higher burden of adverse post‐operative outcomes, especially in left ventricular assist device (LVAD) recipients. IABP, Intra‐aortic balloon pump; VA‐ECMO, veno‐arterial extracorporeal membrane oxygenation.